THE USE OF TRITON X-100 ABSOLUTE WITH VARIATIONS OF IMMERSION TIME IN THE DECELLULARIZATION PROCESS OF INTESTINAL AND MYOCARDIAL XENOGRAFT - Permata, Fajar Shodiq; Paramanandi, Dini Agusti; Nobilla, Nadia; Manalu, Rahel Oktarina; Amalia, Mifta Rizqina (Jurnal Kedokteran Hewan, 2024)
This study aims to determine the comparison of residual cells in the extracellular matrix of goat myocardium and intestinal segments after immersion in Triton X-100. A total of 20 goat myocardial segments (1x1x0.5 cm) and 20 goat intestinal segments (1x0.5x0.5cm) were divided into 4 treatment groups, namely the decellularization immersion groups for 24 hours, 48 hours, 72 hours and the control group without decellularization. In this research, the emersion technique was used by immersed the samples in 5 mL of absolute Triton X-100 solution. The samples were subjected to Hematoxylin-Eosin (HE) and Mallory staining. The HE staining showed a considerable number of nuclei remained in all of the treatment groups, in the control group, 24-hour group of treatment, 48-hour group of treatment and 72-hour group of treatment. An observation using Mallory staining showed an intact extracellular matrix in tissue samples following the immersion with absolute Triton X-100. Therefore, it can be concluded that the immersion using absolute Triton X-100 could not completely remove the extracellular matrix in the decellularization process until 72 hours of immersion.